2002
DOI: 10.1073/pnas.132393999
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome comparative analysis of three phytopathogenic Xylella fastidiosa strains

Abstract: Xylella fastidiosa (Xf ) causes wilt disease in plants and is responsible for major economic and crop losses globally. Owing to the public importance of this phytopathogen we embarked on a comparative analysis of the complete genome of Xf pv citrus and the partial genomes of two recently sequenced strains of this species: Xf pv almond and Xf pv oleander, which cause leaf scorch in almond and oleander plants, respectively. We report a reanalysis of the previously sequenced Xf 9a5c (CVC, citrus) strain and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
20

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 30 publications
2
67
0
20
Order By: Relevance
“…Comparative prophage analysis in bacterial species that were sequenced in multiple strains (Streptococcus, Staphylococcus, and Salmonella strains) or in sister species (Listeria, Xanthomonas, and Xylella) all provided arguments against the maintenance of a given prophage profile over longer evolutionary times. Furthermore, microarray analysis and PCR scanning demonstrated that prophages were generally strain specific within a given bacterial species (7,13,15,39,63,150,161,169). In fact, there are examples from both pathogenic and commensal bacterial species where prophages represented the majority of the strainspecific DNA.…”
Section: Age Of the Prophagesmentioning
confidence: 99%
“…Comparative prophage analysis in bacterial species that were sequenced in multiple strains (Streptococcus, Staphylococcus, and Salmonella strains) or in sister species (Listeria, Xanthomonas, and Xylella) all provided arguments against the maintenance of a given prophage profile over longer evolutionary times. Furthermore, microarray analysis and PCR scanning demonstrated that prophages were generally strain specific within a given bacterial species (7,13,15,39,63,150,161,169). In fact, there are examples from both pathogenic and commensal bacterial species where prophages represented the majority of the strainspecific DNA.…”
Section: Age Of the Prophagesmentioning
confidence: 99%
“…Published annotations indicate that these genomes each contain from 2,066 to 2,294 protein-coding sequences, 2 ribosomal RNA operons, 49-50 tRNA genes (43 different anti-codons), and 1 tmRNA gene (van Sluys et al 2003). Draft quality genomes are available for three other isolates, each appearing to be very similar to one of the finished genomes at the coarse scale (Bhattacharyya et al 2002;Schreiber et al 2010;Zhang et al 2011), as are contigs from the shotgun sequencing of a mixed sample of subspecies multiplex and sandyi (Bhattacharyya et al 2002;Nunney et al 2012). The diversity of available sequences will increase rapidly in the near future, as several projects are underway that are sequencing tens of genomes from isolates collected around the world.…”
Section: 3mentioning
confidence: 99%
“…Recent genome comparisons involving Xf strains obtained from citrus, almond, and oleander plants broadened this scenario, suggesting that a series of conjugation-related ORFs found in Xf strains could have been acquired from soil-inhabiting bacteria (Bhattacharyya et al 2002a). Moreover, a large (∼67-kb) element present in the genome of Xf strain 9a5c was identified as a new prophage, probably derived from the Siphophage group of doublestranded bacteriophages (Bhattacharyya et al 2002b).…”
Section: Genomic Comparison Of Xf Strainsmentioning
confidence: 99%